The Team Work Equipment Sdn. Bhd. / Dzul Hizzam Zainal ... [et al.] - Zainal, Dzul Hizzam; Elias, Elianis; Mohamed, Maizatul Kamisah; Ku Mohamad, Ku Sitiaishah; Nan, Norazila (Faculty of Artistic and Creative Technology, 2003)
The Team Work Equipment Sdn. Bhd will be establish on January 2004. The Team Work Equipment Sdn. Bhd are located at No. 15, Jalan Togo 8, Taman Perindustrian Togo,Sri Damansara, 52200 Kuala Lumpur, Malaysia.